Hepatic Transcriptome Responses of Domesticated and Wild Turkey Embryos to Aflatoxin B1 - Melissa S. Monson (Toxins, 2016)
The mycotoxin, aflatoxin B1 (AFB1) is a hepatotoxic, immunotoxic, and mutagenic contaminant of food and animal feeds. In poultry, AFB1 can be maternally transferred to embryonated eggs, affecting development, viability and performance after hatch. Domesticated turkeys (Meleagris gallopavo) are especially sensitive to aflatoxicosis, while Eastern wild turkeys (M. g. silvestris) are likely more resistant. In ovo exposure provided a controlled AFB1 challenge and comparison of domesticated and wild turkeys. Gene expression responses to AFB1 in the embryonic hepatic transcriptome were examined using RNA-sequencing (RNA-seq). Eggs were injected with AFB1 (1 μg) or sham control and dissected for liver tissue after 1 day or 5 days of exposure. Libraries from domesticated turkey (n = 24) and wild turkey (n = 15) produced 89.2 Gb of sequence. Approximately 670 M reads were mapped to a turkey gene set. Differential expression analysis identified 1535 significant genes with |log2 fold change| ≥ 1.0 in at least one pair-wise comparison. AFB1 effects were dependent on exposure time and turkey type, occurred more rapidly in domesticated turkeys, and led to notable up-regulation in cell cycle regulators, NRF2-mediated response genes and coagulation factors. Further investigation of NRF2-response genes may identify targets to improve poultry resistance.